(untitled) (Research, Society and Development, 2023)
Introduction: Studies suggest deleterious effects on proprioception and muscular performance in individuals after reducing the temperature of muscle groups in the lower limbs.Objectives: To analyze the effects of intermittent cryocompression on the functional performance of physiotherapy students.Methodology: Randomized controlled clinical trial involving students from the physiotherapy course. The participants were randomly divided into two groups: Group 1 (G1) and Group 2 (G2). G1 participants in the Intervention Phase performed the pre-defined functional tests (T0) and then underwent intermittent cryocompression with the Game Ready®, adjusted to 1ºC, for 10 minutes, and were evaluated again as soon as cryotherapy was completed (T1) and after 30 minutes (T2).In the Control Phase, they returned to perform only functional tests. G2 started in the Control Phase, carrying out only functional tests and in the Intervention Phase they carried out tests and intermittent cryocompression with Game Ready®. The Drop Jump (DJ) and Counter Movement Jump (CMJ) tests were used to evaluate parameters such as power and explosive strength.Results: No statistically significant difference was observed between the test values ​​of the control and intervention data for the CMJ and DJ data. Conclusion: Based on the results of this study, intermittent cryocompression does not seem to have significant effects on the functional performance of physiotherapy students during the execution of CMJ and DJ functional tests.